Socialization of the Impact of Fast Food Consumption on Adolescent Health in School Environments - Irmayani Irmayani; Rosita Ginting; Sri Melda Bangun; Jul Asdar Putra Samura; Surya Darma; Siti Sarah Bitang (JURNAL PENGMAS KESTRA (JPK), 2026)
Background: Adolescents are an age group experiencing various behavioral changes, including changes in food consumption patterns influenced by technological advances, social environments, and modern lifestyles. One of the changes that is often found is the increase in fast food consumption. Excessive fast food consumption can have negative impacts on health, including increasing the risk of obesity, hypertension, diabetes mellitus, dyslipidemia, digestive disorders, and various other non-communicable diseases. Low knowledge about the health impacts of fast food consumption is also a factor that causes this consumption behavior to continue to increase, so efforts are needed to increase adolescent awareness about the importance of healthy eating patterns. Objective: This community service activity aims to increase the level of knowledge and awareness of students regarding the impact of fast food consumption on health through the implementation of a health education program. The activity was carried out at MTsN 2 Deli Serdang Regency, involving 45 students as participants. Method: The approach used includes delivering material through health counseling using presentation media and leaflets, interactive discussions, question and answer sessions, and knowledge evaluation through pre-tests and post-tests. Results: There was an increase in participants' knowledge after participating in the socialization activity with an average pre-test score of 44.4 increasing to 88.9 in the post-test, indicating an increase in knowledge of 44.5 points. The results of the activity indicate that health socialization is effective in increasing adolescents' knowledge and awareness regarding the negative impacts of fast food consumption on health. This increased understanding is expected to encourage the formation of healthier eating behaviors as a preventive measure to reduce the risk of various diseases in the future.